Pengaruh Komitmen Organisasional dan Motivasi Kerja Terhadap Kepuasan Kerja Pegawai (Studi Kasus pada Kantor PDAM Kab.Brebes) - Dewi Larasati, 10.05.51.0045; Sutomo, Yohanes (Students Journal of Economic and Management, 2014)
The purpose of this study is: Analyze and explain the influence of organizational commitment on job satisfaction at the Office of PDAM Regency Brebes, as well as Analyze and explain the influence of work motivation on job satisfaction at the Office of PDAM Regency Brebes. This research was conducted at the Office of PDAM Regency Brebes. According to the existing population inÂ Office taps about 151 employees, researchers took a sample of 90 respondents to the research process. After distributing questionnaires to 90 respondents, overall questionnaires were returned with true and good there are 90 respondents. From this study, organizational commitment and motivation to work equally positive influence on job satisfaction, but higher levels are influencing organizational commitment. This means about attitudes and organizational behavior as an indicator of organizational commitment are able to provide direction to employees in identifying themselves in the company and is responsible for his work. Keywords: Organizational Commitment, Work Motivation and Job Satisfaction